Early acquisition of complex syntax in Mandarin-speaking infants - Jingtao Zhu; Anna Gavarró (Scientific Reports)
Abstract Although Mandarin is an S(ubject)V(erb)O(bject) language, other non-canonical sentences with the object marker ba are also possible, yet their comprehension in child Mandarin is underexplored. This study uses eye-tracking and the intermodal preferential looking paradigm, as well as the use of pseudo-verbs, to explore how 24 Mandarin infants (mean age: 17.5 months) and 48 adults process these structures. The results of our experiments show that both infants and adults looked longer at the target scenes for the three grammatical sentence types tested: SVO, SbaOV and O, SbaOV. While comprehension of SVO and SbaOV could be achieved with an agent-first parsing strategy, the fact that patient-first O, SbaOV constructions were also parsed by infants suggests access to grammatical, language-specific knowledge.